Only daughter [large type] - Snoekstra, Anna (Thorndike Press, 2017)
"In 2003, sixteen-year-old Rebecca Winter disappeared. She'd been enjoying her summer break: working at a fast-food restaurant, crushing on an older boy and shoplifting with her best friend. Mysteriously ominous things began to happen--a presence in her room at night, periods of blackouts, a feeling of being watched--though Bec remained oblivious of what was to come. Eleven years later she is replaced. A young woman, desperate after being arrested, claims to be the decade-missing Bec. Soon the impostor is living Bec's life. Sleeping in her bed. Hugging her mother and father. Learning her best friends' names. Playing with her little brothers. But Bec's welcoming family and enthusiastic friends are not quite as they seem. As the impostor dodges the detective investigating her case, she begins to delve into the life of the real Bec Winter and soon realizes that whoever took Bec is still at large, and that she is in imminent danger."--Amazon.com